Bakuchiol Attenuates Oxidative Stress and Neuron Damage by Regulating Trx1/TXNIP and the Phosphorylation of AMPK After Subarachnoid Hemorrhage in Mice - Haixiao Liu; Haixiao Liu; Wei Guo; Hao Guo; Lei Zhao; Liang Yue; Xia Li; Dayun Feng; Jianing Luo; Xun Wu; Wenxing Cui; Yan Qu (Frontiers Media S.A., 2020)
Subarachnoid hemorrhage (SAH) is a fatal cerebrovascular condition with complex pathophysiology that reduces brain perfusion and causes cerebral functional impairments. An increasing number of studies indicate that early brain injury (EBI), which occurs within the first 72 h of SAH, plays a crucial role in the poor prognosis of SAH. Bakuchiol (Bak) has been demonstrated to have multiorgan protective effects owing to its antioxidative and anti-inflammatory properties. The present study was designed to investigate the effects of Bak on EBI after SAH and its underlying mechanisms. In this study, 428 adult male C57BL/6J mice weighing 20 to 25 g were observed to investigate the effects of Bak administration in an SAH animal model. The neurological function and brain edema were assessed. Content of MDA/3-NT/8-OHdG/superoxide anion and the activity of SOD and GSH-Px were tested. The function of the blood-brain barrier (BBB) and the protein levels of claudin-5, occludin, zonula occludens-1, and matrix metalloproteinase-9 were observed. TUNEL staining and Fluoro-Jade C staining were conducted to evaluate the death of neurons. Ultrastructural changes of the neurons were observed under the transmission electron microscope. Finally, the roles of Trx, TXNIP, and AMPK in the protective effect of Bak were investigated. The data showed that Bak administration 1) increased the survival rate and alleviated neurological functional deficits; 2) alleviated BBB disruption and brain edema; 3) attenuated oxidative stress by reducing reactive oxygen species, MDA, 3-NT, 8-OHdG, gp91phox, and 4-HNE; increased the activities of SOD and GSH-Px; and alleviated the damage to the ultrastructure of mitochondria; 4) inhibited cellular apoptosis by regulating the protein levels of Bcl-2, Bax, and cleaved caspase-3; and 5) upregulated the protein levels of Trx1 as well as the phosphorylation of AMPK and downregulated the protein levels of TXNIP. Moreover, the protective effects of Bak were partially reversed by PX-12 and compound C. To summarize, Bak attenuates EBI after SAH by alleviating BBB disruption, oxidative stress, and apoptosis via regulating Trx1/TXNIP expression and the phosphorylation of AMPK. Its powerful protective effects might make Bak a promising novel drug for the treatment of EBI after SAH.